Pengembangangan Alat Penyiram Otomatis Dan Monitoring Budidaya Cabe Merah Berbasis Internet Of Things (Iot) - Miftahul Walid; Sohibul Burhan (Fakultas Teknik, 2023)
Technology of today has improved a number of spheres of life, including governance, agriculture, and education. Information technology use tries to provide efficiency in a number of ways. Given Indonesia's low level of technological development, particularly in the area of agriculture, innovation is unquestionably required if this country is to be competitive on the global stage. This is especially true in this era of globalization. Clearly, the agriculture sector has to develop technology that makes human labor more efficient and effective. Traditional farmers can benefit from technology in their operations to produce better yields and greater volumes. Red chili is one of the key agricultural products that needs to be developed because it has a high economic value, is a superior national and regional product, and occupies a significant place in the menu due to the fact that almost the entire population of Indonesia consumes it every day, albeit in small amounts. This plant can grow to a height of mdpl in both the lowlands and the highlands, but the lowlands are where it grows the best. The ideal air temperature range for growing chile plants is 18°C to 28°C. Fertilization might be hindered by temperatures between 16 and 32 degrees Celsius. The soil wetness of chili plants ranges between 60% and 80%. When limited space is available, growing red chilies either directly or in pots can be a solution. are hard to come by, especially for family needs. For farmers or plant owners, smart garden technology works and offers advantages, as well as a way to communicate with plants.